Electromagnetic wave absorbing sheet

The electromagnetic wave absorbing sheet, featuring a fibrous substrate with adhered carbon nanotubes, addresses the challenge of limited high-frequency absorption by achieving superior performance with a transmission attenuation rate of 40 dB or more in the specified frequency range.

JP7666929B2Active Publication Date: 2025-04-22ZEON CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2020569626
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-01-28
Filing Date
2020-01-28
Publication Date
2025-04-22
Estimated Expiration
2040-01-28

AI Technical Summary

Technical Problem

Existing electromagnetic wave absorbers have limited performance in absorbing high-frequency electromagnetic waves, necessitating the development of a sheet with enhanced absorption capabilities in this frequency range.

Method used

An electromagnetic wave absorbing sheet is created with a sheet-like fibrous substrate and a plurality of carbon nanotubes adhered to it, with a carbon nanotube adhesion amount of 5% by mass or more and a surface resistance of 20Ω/sq. or more, optimizing absorption performance in the high-frequency region.

Benefits of technology

The sheet achieves excellent electromagnetic wave absorption performance in the high-frequency region, as evidenced by a transmission attenuation rate of 40 dB or more in the range of 10 GHz to 40 GHz, making it suitable for applications in mobile devices and other electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666929000002
    Figure 0007666929000002
  • Figure 0007666929000001
    Figure 0007666929000001
Patent Text Reader

Abstract

The electromagnetic wave absorbing sheet includes a sheet-like fibrous substrate and a plurality of carbon nanotubes attached to the sheet-like fibrous substrate. The carbon nanotube attachment amount in the electromagnetic wave absorbing sheet is 5% by mass or more. The surface resistance of the electromagnetic wave absorbing sheet is 20 Ω / sq. or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electromagnetic wave absorbing sheet, and more particularly to an electromagnetic wave absorbing sheet containing carbon nanotubes. [Background technology]

[0002] Electromagnetic waves are used in a wide variety of fields, including communication devices. In these fields, the frequencies used vary depending on the application, but in actual usage environments, electromagnetic waves in frequency ranges other than the required frequency range can often become noise. For this reason, electromagnetic wave absorbing sheets have been used to block electromagnetic waves in unnecessary frequency ranges that can become noise.

[0003] In recent years, the use of electromagnetic waves in higher frequency ranges has been actively studied. Accordingly, electromagnetic wave absorbers with high absorption performance for electromagnetic waves in higher frequency ranges have been proposed (see, for example, Patent Document 1). Patent Document 1 proposes an electromagnetic wave absorber having a fibrous base material and carbon nanotubes attached to the base material, which satisfies a predetermined basis weight, porosity, conductivity, relative dielectric constant, etc. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2015 / 093600 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the electromagnetic wave absorbers proposed so far as described above have room for improvement in terms of electromagnetic wave absorbing performance in the high frequency range.

[0006] Therefore, an object of the present invention is to provide an electromagnetic wave absorbing sheet that has excellent electromagnetic wave absorbing performance in the high frequency range. [Means for solving the problem]

[0007] The present inventors have conducted extensive research with the aim of solving the above problems, and have found that by making the amount of carbon nanotubes attached to an electromagnetic wave absorbing sheet equal to or greater than a predetermined value and by making the surface resistance of the sheet equal to or greater than a predetermined value, it is possible to improve the electromagnetic wave absorbing performance in the high frequency range, thereby completing the present invention.

[0008] That is, the present invention aims to advantageously solve the above problems, and the electromagnetic wave absorbing sheet of the present invention is an electromagnetic wave absorbing sheet including a sheet-like fibrous substrate and a plurality of carbon nanotubes attached to the sheet-like fibrous substrate, characterized in that the carbon nanotube attachment amount is 5% by mass or more and the surface resistance is 20Ω / sq. or more. In this way, in an electromagnetic wave absorbing sheet in which carbon nanotubes are attached to a sheet-like fibrous substrate, if the carbon nanotube attachment amount is 5% by mass or more and the surface resistance is 20Ω / sq. or more, the electromagnetic wave absorbing performance in the high frequency range is excellent. The carbon nanotube attachment amount in the electromagnetic wave absorbing sheet is a value indicating the occupancy rate (mass%) of the carbon nanotubes contained in the electromagnetic wave absorbing sheet when the total mass of the electromagnetic wave absorbing sheet is taken as 100% by mass, and can be measured by the method described in the Examples. The surface resistance of the electromagnetic wave absorbing sheet can be measured by implementing a four-probe method in which a probe is placed on one side of the electromagnetic wave absorbing sheet according to JIS K 7194.

[0009] Here, the electromagnetic wave absorbing sheet of the present invention preferably has a thickness of 100 μm or less. If the electromagnetic wave absorbing sheet has a thickness of 100 μm or less, it can be suitably used in mobile terminals such as smartphones and tablets, and in various applications where space saving is required. The thickness of the electromagnetic wave absorbing sheet can be measured by the method described in the examples.

[0010] Furthermore, in the electromagnetic wave absorbing sheet of the present invention, the BET specific surface area of ​​the carbon nanotubes is 600 m 2 The electromagnetic wave absorbing sheet preferably has a BET specific surface area of ​​600 m 2 / g or more, the electromagnetic wave absorption performance in the high frequency range is further improved. In this specification, the "BET specific surface area" refers to the nitrogen adsorption specific surface area measured using the BET (Brunauer-Emmett-Teller) method.

[0011] Furthermore, in the electromagnetic wave absorbing sheet of the present invention, the sheet-like fibrous base material has a basis weight of 80 g / m 2 The nonwoven fabric preferably has a basis weight of 80 g / m2 or less. 2 The nonwoven fabric below has even better electromagnetic wave absorption performance in the high frequency range. Note that "basis weight" refers to the mass of the nonwoven fabric per unit area.

[0012] Another example of the electromagnetic wave absorbing sheet of the present invention is characterized in that the transmission attenuation rate in the range of 10 GHz to 40 GHz is 40 dB or more. An electromagnetic wave absorbing sheet that satisfies such attributes has excellent electromagnetic wave absorption performance in the high frequency range. The "transmission attenuation rate" value in the range of 10 GHz to 40 GHz can be measured by the method described in the Examples. Effect of the Invention

[0013] According to the present invention, it is possible to provide an electromagnetic wave absorbing sheet that has excellent electromagnetic wave absorbing performance in the high frequency range. [Brief description of the drawings]

[0014] [Figure 1] 1 is a graph showing the results of evaluating the electromagnetic wave absorbing performance of the electromagnetic wave absorbing sheets obtained in Example 1 and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The electromagnetic wave absorbing sheet of the present invention is preferably used as a noise suppression sheet that can be mounted on mobile terminals and other electronic devices to suppress high frequency noise.

[0016] (Electromagnetic wave absorbing sheet) An example of the electromagnetic wave absorbing sheet of the present invention (hereinafter also simply referred to as "electromagnetic wave absorbing sheet of the present invention") is an electromagnetic wave absorbing sheet comprising a sheet-like fibrous substrate and a plurality of carbon nanotubes attached to the sheet-like fibrous substrate. The electromagnetic wave absorbing sheet of the present invention is characterized in that the amount of carbon nanotubes attached is 5 mass % or more and the surface resistance is 20 Ω / sq. or more. The electromagnetic wave absorbing sheet of the present invention may optionally contain other components such as additives used during the production of the electromagnetic wave absorbing sheet. The electromagnetic wave absorbing sheet of the present invention can exhibit excellent electromagnetic wave absorbing performance in the high frequency range.

[0017] In addition, carbon nanotubes are usually attached to the fibers constituting the sheet-like fibrous substrate. Here, carbon nanotubes "attached" to the fibers constituting the sheet-like fibrous substrate means a state in which carbon nanotubes are attached or entangled on the fibers that are the constituent units of the sheet-like fibrous substrate. In the electromagnetic wave absorbing sheet of the present invention, it is preferable that carbon nanotubes are usually attached not only to the fibers located on the surface of the sheet-like fibrous substrate but also to the fibers located on the inner side in the thickness direction of the sheet-like fibrous substrate. In particular, the electromagnetic wave absorbing sheet of the present invention is considered to absorb electromagnetic waves by attenuating the incident electromagnetic waves by diffuse reflection inside the sheet, by carbon nanotubes attached to the fibers located on the inner side in the thickness direction of the sheet-like fibrous substrate.

[0018] <Fibrous base material in sheet form> As a sheet-like fibrous substrate that can be used for the electromagnetic wave absorbing sheet, a sheet-like fibrous substrate made of fibers, especially organic fibers, can be suitably used. Note that carbon nanotubes are not included in the above-mentioned organic fibers. The organic fibers that can be used to form the sheet-like fibrous substrate are not particularly limited, and examples thereof include synthetic fibers made of polymers such as polyvinyl alcohol, vinylon, polyethylene vinyl alcohol, polyethylene glycol, polyvinylpyrrolidone, poly-ε-caprolactone, polyacrylonitrile, polylactic acid, polycarbonate, polyamide, polyimide, polyethylene, polypropylene, polyethylene terephthalate, and modified products thereof; natural fibers such as cotton, hemp, wool, and silk; and the like. As the polymers that form the synthetic fibers, one type can be used alone, or multiple types can be used in combination. Among these, synthetic fibers are preferred as the organic fibers, and vinylon, which is an acetalized product of polyvinyl alcohol, is more preferred. The sheet-like fibrous substrate can be a woven fabric or nonwoven fabric that can be formed from these organic fibers. Among these, the sheet-like fibrous substrate is preferably a nonwoven fabric. In this specification, the term "nonwoven fabric" refers to "a fiber sheet, web or batt in which the fibers are oriented in one direction or randomly and are bonded by at least one of entanglement, fusion and adhesion" as defined in JIS L 0222:2001 (however, excluding paper, woven fabric, knitted fabric, tufted fabric and crepe felt).

[0019] The basis weight of the sheet-like fibrous base material is 80 g / m 2 It is preferable that the thickness is less than 50 g / m 2 More preferably, it is 30 g / m or less. 2 It is even more preferable that the basis weight is equal to or less than the upper limit. If the basis weight is equal to or less than the upper limit, an electromagnetic wave absorbing sheet can be obtained in which the carbon nanotubes are well attached inside the sheet. As a result, the electromagnetic wave absorbing performance in the high frequency range of the electromagnetic wave absorbing sheet can be further improved. Also, from the viewpoint of the recent demand for lightweight electromagnetic wave absorbing sheets, it is preferable that the basis weight is equal to or less than the upper limit. In order to increase the mechanical strength of the electromagnetic wave absorbing sheet and to further improve the electromagnetic wave absorbing performance in the high frequency range, the basis weight of the nonwoven fabric as the sheet-like fibrous substrate is set to 2 g / m. 2 It is preferable that the content is 6 g / m or more. 2 More preferably, it is equal to or greater than this. From the viewpoint of further improving the electromagnetic wave absorbing performance of the electromagnetic wave absorbing sheet in the high frequency range, when a nonwoven fabric is used as the sheet-like fibrous substrate, it is particularly preferable that the basis weight of the nonwoven fabric satisfies the above-mentioned suitable range.

[0020] <Carbon nanotubes> The carbon nanotubes (hereinafter, sometimes referred to as CNTs) contained in the electromagnetic wave absorbing sheet of the present invention preferably contain single-walled carbon nanotubes (single-walled CNTs) as a main component. An example of a component other than single-walled CNTs that may be contained in CNTs is multi-walled carbon nanotubes (multi-walled CNTs). Here, the ratio of single-walled CNTs to the total mass of CNTs is preferably more than 50 mass%, more preferably 90 mass% or more, even more preferably 95 mass% or more, and may be 100 mass%. Note that, when the CNTs contain multi-walled CNTs, the number of walls of the multi-walled CNTs is preferably 5 or less.

[0021] Preferred attributes of CNTs are described below, and these attributes preferably apply to both the CNTs used as a material in producing the electromagnetic wave absorbing sheet of the present invention and the CNTs contained in the electromagnetic wave absorbing sheet of the present invention. More specifically, at least the BET specific surface area and average diameter, etc., do not fall below the values ​​exhibited by the CNTs as a material, in principle, even after undergoing various treatments included in the production method of the electromagnetic wave absorbing sheet described below.

[0022] CNTs can be produced by known CNT synthesis methods such as arc discharge, laser ablation, and chemical vapor deposition (CVD), without any particular limitation. Specifically, CNTs can be efficiently produced in accordance with a method (super growth method; see International Publication No. 2006 / 011655) in which, for example, a raw material compound and a carrier gas are supplied onto a substrate having a catalyst layer for producing carbon nanotubes on its surface, and a trace amount of an oxidizing agent (catalyst activation material) is made present in the system when synthesizing CNTs by chemical vapor deposition (CVD), dramatically improving the catalytic activity of the catalyst layer. In the following, carbon nanotubes obtained by the super growth method may be referred to as "SGCNTs".

[0023] Furthermore, it is preferable that the CNTs have a t-plot obtained from the adsorption isotherm that shows an upwardly convex shape. As such CNTs, it is more preferable that the CNTs are not subjected to an opening treatment.

[0024] Here, in a material having pores on the surface, the growth of a nitrogen gas adsorption layer is classified into the following processes (1) to (3). The slope of the t-plot changes depending on the processes (1) to (3) below. (1) The process of forming a monolayer of nitrogen molecules on the entire surface (2) Formation of multilayer adsorption and the associated capillary condensation filling process in the pores (3) The formation of multilayer adsorption on an apparently non-porous surface whose pores are filled with nitrogen

[0025] In the t-plot showing an upward convex shape, the plot is located on a straight line passing through the origin in the region where the average thickness t of the nitrogen gas adsorption layer is small, whereas as t increases, the plot is shifted downward from the straight line. CNTs having such a t-plot shape have a large ratio of the internal specific surface area to the total specific surface area of ​​the CNTs, indicating that many openings are formed in the CNTs. As a result, when a dispersion is prepared using such CNTs, the CNTs are less likely to aggregate in the dispersion, and an electromagnetic wave absorbing sheet that is homogeneous and has even better electromagnetic wave absorbing performance in the high frequency region can be obtained.

[0026] The bending point of the t-plot of the CNT is preferably in a range satisfying 0.2≦t(nm)≦1.5, more preferably in the range of 0.45≦t(nm)≦1.5, and even more preferably in the range of 0.55≦t(nm)≦1.0. When a dispersion is prepared using CNTs having a bending point of the t-plot in such a range, the CNTs are less likely to aggregate in the dispersion. As a result, an electromagnetic wave absorbing sheet that is more homogeneous and has more excellent electromagnetic wave absorbing performance in the high frequency range can be obtained. Here, the "position of the bending point" is the intersection point between the approximation line A in the above-mentioned process (1) and the approximation line B in the above-mentioned process (3).

[0027] Furthermore, the CNTs preferably have a ratio (S2 / S1) of the internal specific surface area S2 to the total specific surface area S1 obtained from the t-plot of 0.05 to 0.30. When a dispersion is prepared using CNTs having a value of S2 / S1 within this range, the CNTs are less likely to aggregate in the dispersion. As a result, an electromagnetic wave absorbing sheet that is more homogeneous and has more excellent electromagnetic wave absorbing performance in the high frequency range can be obtained.

[0028] Here, the total specific surface area S1 and the internal specific surface area S2 of the CNTs can be obtained from the t-plot. Specifically, first, the total specific surface area S1 can be obtained from the slope of the approximation line in step (1), and the external specific surface area S3 can be obtained from the slope of the approximation line in step (3). Then, the internal specific surface area S2 can be calculated by subtracting the external specific surface area S3 from the total specific surface area S1.

[0029] The measurement of the adsorption isotherm of the CNTs, the creation of t-plots, and the calculation of the total specific surface area S1 and the internal specific surface area S2 based on the analysis of the t-plots can be performed using, for example, a commercially available measuring device, "BELSORP (registered trademark)-mini" (manufactured by BEL JAPAN, Inc.).

[0030] In addition, CNTs have a BET specific surface area of ​​600 m 2 / g or more, and 2 / g or more is more preferable, and 2000m 2 / g or less, and 2 / g or less is more preferable, and 1600m 2 When the BET specific surface area is within the above range, the electromagnetic wave absorbing sheet can exhibit even more excellent electromagnetic wave absorbing performance in the high frequency range.

[0031] The average diameter of the CNTs is preferably 1 nm or more, and is preferably 60 nm or less, more preferably 30 nm or less, and even more preferably 10 nm or less. Furthermore, the average length of the CNTs is preferably 10 μm or more, more preferably 50 μm or more, and even more preferably 80 μm or more, and is preferably 600 μm or less, more preferably 500 μm or less, and even more preferably 400 μm or less. When a dispersion is prepared using CNTs whose average diameter and / or average length are within the above ranges, the CNTs are less likely to aggregate in the dispersion, making it possible to obtain an electromagnetic wave absorbing sheet that is homogeneous and has even better electromagnetic wave absorbing performance in the high frequency range.

[0032] Furthermore, CNTs typically have an aspect ratio (length / diameter) greater than 10. The average diameter, average length and aspect ratio of CNTs can be determined by measuring the diameter and length of 100 randomly selected CNTs using a scanning electron microscope or a transmission electron microscope.

[0033] Single-walled CNTs, in which the t-plot obtained from the adsorption isotherm shows an upwardly convex shape, can be efficiently produced by the above-mentioned super-growth method, by forming a catalyst layer on the substrate surface using a wet process.

[0034] <Carbon nanotube adhesion amount> The carbon nanotube attachment amount in the electromagnetic wave absorbing sheet of the present invention must be 5% by mass or more, preferably 7% by mass or more, more preferably 10% by mass or more, and preferably less than 70% by mass, and more preferably 65% ​​by mass or less. If the carbon nanotube attachment amount is 5% by mass or more, it means that the electromagnetic wave absorbing sheet contains a necessary and sufficient amount of carbon nanotubes to exhibit electromagnetic wave absorbing performance. Furthermore, if the carbon nanotube attachment amount is within the above-mentioned preferable range, the electromagnetic wave absorbing performance in the high frequency range of the electromagnetic wave absorbing sheet can be further improved.

[0035] <Surface resistance> The surface resistance of the electromagnetic wave absorbing sheet of the present invention must be 20 Ω / sq. or more, and is preferably 100 Ω / sq. or more. If the surface resistance of the electromagnetic wave absorbing sheet is 20 Ω / sq. or more, it means that the carbon nanotubes are not concentrated and attached to the sheet surface. Since carbon nanotubes are conductive materials, if the carbon nanotubes are concentrated and attached to the sheet surface and exist in a state as if they form a "layer", such a sheet has excellent conductivity in the surface direction, so the surface resistance of the sheet can be low. In this case, it is considered that the electromagnetic waves incident on the sheet surface are reflected by the sheet surface and are difficult to penetrate into the inside of the sheet. Here, as described above, the electromagnetic wave absorbing sheet of the present invention has a surface resistance of 20 Ω / sq. or more. This means that the carbon nanotubes are not attached to the surface of the electromagnetic wave absorbing sheet so as to form a "layer". If the carbon nanotubes do not form a "layer" on the surface of the electromagnetic wave absorbing sheet, but are also present inside the electromagnetic wave absorbing sheet in the thickness direction, the electromagnetic waves that penetrate into the sheet can be diffusely reflected between the multiple carbon nanotubes inside the sheet. As a result, the electromagnetic waves can be attenuated inside the sheet due to such diffuse reflection. The upper limit of the surface resistance is not particularly limited, but can be, for example, 4000 Ω / sq. or less.

[0036] <Electromagnetic wave absorption performance> The electromagnetic wave absorbing sheet of the present invention preferably has a transmission attenuation rate (Rtp) value of 30 dB or more at 30 GHz, and more preferably 40 dB or more. An electromagnetic wave absorbing sheet capable of exhibiting such electromagnetic wave absorbing performance can be used very well in applications requiring high electromagnetic wave absorbing performance in the high frequency range. Furthermore, the electromagnetic wave absorbing sheet of the present invention preferably has a transmission attenuation rate value of 40 dB or more in the range of 10 GHz to 40 GHz.

[0037] <Thickness> The thickness of the electromagnetic wave absorption sheet of the present invention is preferably 100 μm or less, more preferably 68 μm or less, and even more preferably 60 μm or less. If the thickness of the electromagnetic wave absorption sheet is below the above upper limit, such a thin electromagnetic wave absorption sheet can be suitably used for various applications. Note that the thickness of the electromagnetic wave absorption sheet is preferably 10 μm or more. If the thickness of the electromagnetic wave absorption sheet is above the above lower limit, the electromagnetic wave absorption sheet can have sufficient mechanical strength and exhibit even better electromagnetic wave absorption performance in the high-frequency region.

[0038] <Manufacturing method> The electromagnetic wave absorption sheet can be manufactured by performing steps such as dipping a fibrous substrate into a dispersion liquid of carbon nanotubes (CNT dispersion liquid dipping step), pulling up and washing the dipped fibrous substrate (washing step), and drying the washed fibrous substrate (drying step). Hereinafter, an outline of the manufacturing method according to an example will be described.

[0039] <<CNT dispersion liquid dipping step>> In the CNT dispersion liquid dipping step, a fibrous substrate is dipped into a dispersion liquid of carbon nanotubes. As the fibrous substrate, those described above in the item of <sheet-like fibrous substrate> can be preferably used. The dispersion liquid of carbon nanotubes (CNT dispersion liquid) can be prepared by dispersing CNTs in a dispersion medium. Also, as the CNTs, those described above in the item of <carbon nanotubes> can be preferably used. The dispersion medium is not particularly limited, and water, isopropanol (2-propanol), 1-methyl-2-pyrrolidone, dimethylformamide, dimethyl sulfoxide, dimethylacetamide, toluene, tetrahydrofuran, ethyl acetate, acetonitrile, ethylene glycol, methyl isobutyl ketone, and butyl alcohol can be used. Among them, it is preferable to use water as the dispersion medium.

[0040] When preparing the CNT dispersion, a dispersant can be added as an additive to improve the dispersibility of CNT in the CNT dispersion. The dispersant is not particularly limited, and for example, known surfactants such as sodium dodecyl sulfonate, sodium deoxycholate, sodium cholate, and sodium dodecylbenzenesulfonate, and various synthetic or natural polymers that can function as dispersants can be used. The amount of the dispersant added can be within a general range.

[0041] In preparing a CNT dispersion, CNTs are added to a dispersion medium containing a surfactant as described above to obtain a crude dispersion, and then the crude dispersion is subjected to a dispersion method that provides a cavitation effect and / or a dispersion method that provides a disintegration effect as disclosed in International Publication No. 2014 / 115560, thereby obtaining a CNT dispersion with good CNT dispersibility. Note that the dispersion method is not limited to these two methods, and it is of course possible to apply a method of directly stirring using a stirrer.

[0042] When preparing the CNT dispersion, other components such as carbon materials other than carbon nanotubes and additives may be optionally added to the CNT dispersion. When other components are added, they may be added to the crude dispersion of CNTs, for example.

[0043] The dispersion time when preparing the CNT dispersion liquid may be, for example, from 1 minute to 120 minutes, and the CNT concentration in the CNT dispersion liquid may be from 0.01 mass % to 0.3 mass %.

[0044] The immersion time when immersing the fibrous substrate in the CNT dispersion liquid obtained as described above is not particularly limited, but may be, for example, 1 minute to 3 hours. The immersion temperature is also not particularly limited, but may be, for example, 0°C to 100°C.

[0045] <<Cleaning process>> In the washing step, the fibrous substrate immersed in the above step is pulled up and washed. As a washing method, a method including an operation of immersing in an alcohol such as isopropanol (2-propanol), ethyl alcohol, or methyl alcohol, and then immersing in water can be preferably adopted. The immersion time in each solvent is not particularly limited, but may be, for example, 1 minute to 3 hours. The immersion temperature in each solvent is also not particularly limited, but may be, for example, 0°C to 100°C.

[0046] <<Drying process>> In the drying step, the fibrous substrate washed in the above step is dried. The drying method is not particularly limited, and examples thereof include hot air drying, vacuum drying, heat roll drying, and infrared irradiation. The drying temperature and drying temperature may be appropriately changed depending on the heat resistance of the fibrous substrate and the boiling point of the liquid used in washing, and are not particularly limited, but are usually room temperature to 200°C, and the drying time is not particularly limited, but is usually 10 minutes to 48 hours.

[0047] In the manufacture of the electromagnetic wave absorbing sheet, the flow from the CNT dispersion liquid immersion step to the drying step is defined as one cycle, and it is preferable to repeat the cycle multiple times or more. This makes it possible to obtain an electromagnetic wave absorbing sheet in which carbon nanotubes are well supported even in the inside of the sheet. The number of cycles is preferably 2 or more, preferably 24 or less, and more preferably 20 or less. If the number of cycles is equal to or greater than the lower limit, the amount of carbon nanotubes attached to the electromagnetic wave absorbing sheet can be sufficiently increased. If the number of cycles is equal to or less than the upper limit, the carbon nanotubes can be prevented from adhering in a "layer" on the surface of the electromagnetic wave absorbing sheet, and the electromagnetic wave absorbing performance in the high frequency range can be efficiently improved.

[0048] The electromagnetic wave absorbing sheet according to another embodiment of the present invention is characterized in that the transmission attenuation rate in the range of 10 GHz to 40 GHz is 40 dB or more. Furthermore, the electromagnetic wave absorbing sheet may include a sheet-like fibrous base material and a plurality of carbon nanotubes attached to the sheet-like fibrous base material. Furthermore, the electromagnetic wave absorbing sheet may have an attachment amount of carbon nanotubes of 5 mass % or more. The electromagnetic wave absorbing sheet according to another embodiment of the present invention has excellent electromagnetic wave absorbing performance in the high frequency range. EXAMPLES

[0049] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples. In the examples and comparative examples, the BET specific surface area of ​​the carbon nanotubes, the amount of carbon nanotubes attached, the thickness of the electromagnetic wave absorbing sheet, the surface resistance of the electromagnetic wave absorbing sheet, and the electromagnetic wave absorption performance of the electromagnetic wave absorbing sheet were measured or calculated using the following methods.

[0050] <BET specific surface area of ​​carbon nanotubes> The nitrogen adsorption specific surface area of ​​the carbon nanotubes used in the examples and comparative examples was measured according to the BET method using "BELSORP (registered trademark)-mini" (manufactured by BEL Japan Co., Ltd.).

[0051] <Carbon nanotube adhesion amount> The amount of carbon nanotubes attached (mass %) in the electromagnetic wave absorbing sheets produced in the examples and comparative examples was calculated based on the following formula using the mass (W0) of the fibrous substrate before carbon nanotubes were attached using an electronic balance, and the mass (W1) of the fibrous substrate (i.e., the electromagnetic wave absorbing sheet) with the carbon nanotubes attached. Carbon nanotube adhesion amount (mass%) = (W1-W0) / W1 x 100

[0052] <Thickness of electromagnetic wave absorbing sheet> The thickness of the electromagnetic wave absorbing sheets produced in the examples and comparative examples was measured using a "Digimatic Standard Outside Micrometer" manufactured by Mitutoyo Corporation.

[0053] <Surface resistance of electromagnetic wave absorbing sheet> For the electromagnetic wave absorbing sheets manufactured in the examples and comparative examples, the surface resistance (Ω / sq.) was calculated using a low resistance resistivity meter ("Loresta (registered trademark) GX" manufactured by Mitsubishi Chemical Analytech Co., Ltd.) in accordance with JIS K 7194:1994 by carrying out a four-probe method in which probes are placed on one side of the sheet.

[0054] <Electromagnetic wave absorbing performance of electromagnetic wave absorbing sheets> For the electromagnetic wave absorbing sheets manufactured in the examples and comparative examples, the reflection coefficient S11 (dB) and the transmission coefficient S21 (dB) were measured by a microstrip line method conforming to IEC-62333, and the transmission attenuation rate Rtp (dB) was calculated using the following formula. Transmission attenuation rate Rtp(dB)=10log 10 {10 S21 / 10 / (1-10 S11 / 10 )} The measurement equipment and measurement frequency range used are as follows. As shown in Table 1, in this evaluation, we focused on the value of the transmission attenuation rate Rtp at 30 GHz. Measurement equipment: Anritsu Vector Network Analyzer 37169A Measurement frequency: 100MHz~40GHz

[0055] Example 1 <Preparation of carbon nanotube dispersion> Sodium dodecylbenzenesulfonate (SDBS) was used as a dispersant and water was used as a dispersion medium to prepare 500 mL of a 1 mass% SDBS aqueous solution. 2 / g, average diameter: 3.3 nm, average length: 400 μm, t-plot is convex upward (position of inflection point: 0.6 nm), internal specific surface area S2 / total specific surface area S1: 0.24), 0.5 g was added to obtain a coarse dispersion containing SDBS as a dispersant. The coarse dispersion containing this single-walled CNT was filled into a high-pressure homogenizer (manufactured by Mikari Co., Ltd., product name "BERYU SYSTEM PRO") having a multi-stage pressure control device (multi-stage pressure reducer) that applies back pressure during dispersion, and the coarse dispersion was dispersed at a pressure of 100 MPa. Specifically, while applying back pressure, a shear force was applied to the coarse dispersion to disperse the CNT, and an SGCNT dispersion with a concentration of 0.1 mass% was obtained. <CNT dispersion immersion step, washing step, drying step> Into 500 mL of the 0.1 mass% SGCNT dispersion obtained as described above, a vinylon nonwoven fabric (basis weight: 12 g / m 2 , thickness: 40 μm) as a sheet-like fibrous substrate of 5 cm × 10 cm was immersed at 30 °C for 10 minutes (CNT dispersion immersion step). Then, the vinylon nonwoven fabric that had undergone the CNT dispersion immersion step was immersed in 500 mL of "2-propanol" manufactured by Wako Pure Chemical Industries, Ltd. at 30 °C for 10 minutes, and then immersed in 500 mL of distilled water for 10 minutes to be washed (washing step). Then, the fibrous substrate with CNTs attached that had undergone the washing step was vacuum-dried at a temperature of 60 °C for 3 hours to obtain a dried product of the fibrous substrate with CNTs attached (drying step). Taking the flow of the above-described CNT dispersion immersion step, washing step, and drying step as one cycle, such a cycle was repeated twice to obtain an electromagnetic wave absorption sheet. For the obtained electromagnetic wave absorption sheet, various measurements were carried out according to the above. The results are shown in Table 1 and FIG. 1. The graph shown in FIG. 1 plots the transmission attenuation rate on the vertical axis and the frequency on the horizontal axis, and is a curve showing the attenuation rate of electromagnetic waves as a function of frequency (hereinafter, may also be referred to as the "attenuation rate curve"). As is clear from FIG. 1, the electromagnetic wave absorption sheet obtained in this example had a transmission attenuation rate (Rtp) of 40 dB or more at 10 GHz to 40 GHz.

[0056] (Examples 2 to 5) An electromagnetic wave absorbing sheet was obtained in the same manner as in Example 1, except that the number of cycles for carrying out the CNT dispersion liquid immersion step, the washing step, and the drying step were changed as shown in Table 1, and the carbon nanotube adhesion amount, surface resistance, thickness, etc. of the obtained electromagnetic wave absorbing sheet were changed as shown in Table 1. Various measurements and calculations were performed on the obtained electromagnetic wave absorbing sheet according to the above-mentioned methods. The results are shown in Table 1. Note that the attenuation curves obtained as a result of the evaluation of the electromagnetic wave absorption performance in these examples showed approximately the same shape as the curve of Example 1 shown in FIG. 1, so are not shown in FIG. 1 for the purpose of clarity of illustration. Note that the electromagnetic wave absorbing sheets obtained in these examples all had a transmission attenuation (Rtp) of 40 dB or more at 10 GHz to 40 GHz.

[0057] (Comparative Examples 1 to 2) An electromagnetic wave absorbing sheet was obtained in the same manner as in Example 1, except that the number of cycles for carrying out the CNT dispersion liquid immersion step, washing step, and drying step were changed as shown in Table 1, and the carbon nanotube adhesion amount, surface resistance, thickness, etc. of the obtained electromagnetic wave absorbing sheet were changed as shown in Table 1. Various measurements and calculations were performed on the obtained electromagnetic wave absorbing sheet according to the above-mentioned methods. The results are shown in Table 1 and Fig. 1. It can be seen from Fig. 1 that the transmission attenuation factor (Rtp) at 10 GHz to 40 GHz was less than 40 dB for both of the electromagnetic wave absorbing sheets obtained in Comparative Examples 1 and 2.

[0058] [Table 1]

[0059] 1, it can be seen that the electromagnetic wave absorbing sheets having a carbon nanotube attachment amount of 5 mass% or more and a surface resistance of 20 Ω / sq. or more had a transmission attenuation (Rtp) value of 45 dB or more at 30 GHz, and had excellent electromagnetic wave absorbing performance in the high frequency range. Also, it can be seen that Comparative Example 1, in which the carbon nanotube attachment amount is less than 5 mass%, and Comparative Example 2, in which the surface resistance is less than 20 Ω / sq., had a transmission attenuation (Rtp) value of 26 dB or less at 30 GHz, and had poor electromagnetic wave absorbing performance in the high frequency range. In particular, it is believed that the amount of carbon nanotubes attached is insufficient in Comparative Example 1, so that the electromagnetic waves pass through the electromagnetic wave absorbing sheet, and therefore the electromagnetic wave absorbing sheet according to Comparative Example 1 is unable to sufficiently absorb high frequency electromagnetic waves. In addition, in Comparative Example 2, from the low surface resistance value, it is considered that the carbon nanotubes form a layer on the surface of the electromagnetic wave absorbing sheet, and therefore, the electromagnetic waves are reflected by the layer of carbon nanotubes on the surface of the electromagnetic wave absorbing sheet, and therefore, it is considered that sufficient electromagnetic wave absorbing performance cannot be exhibited. It is noted that the relationship between the number of cycles and the amount of carbon nanotube attachment in the examples and comparative examples shows that the increase in the amount of carbon nanotube attachment tends to saturate as the number of cycles increases. In the cycle where the increasing trend in the amount of CNT attachment saturates, the carbon nanotubes attached to the fibrous substrate tend to form a layer on the surface of the electromagnetic wave absorbing sheet, which is considered to result in a decrease in the electromagnetic wave absorbing performance of the resulting electromagnetic wave absorbing sheet. [Industrial Applicability]

[0060] According to the present invention, it is possible to provide an electromagnetic wave absorbing sheet that has excellent electromagnetic wave absorbing performance in the high frequency range.

Claims

1. An electromagnetic wave absorbing sheet comprising a sheet-like fibrous substrate and a plurality of carbon nanotubes attached to the sheet-like fibrous substrate, The amount of carbon nanotubes attached is 5 mass% or more, The surface resistance is 20 Ω / sq. or more, the carbon nanotubes are attached to fibers located on the inner side in a thickness direction of the sheet-like fibrous base material, The basis weight of the fibrous base material is 6 g / m 2 or more and 50 g / m2 or less; Electromagnetic wave absorbing sheet.

2. 2. The electromagnetic wave absorbing sheet according to claim 1, having a thickness of 100 μm or less.

3. The BET specific surface area of ​​the carbon nanotubes is 600 m 2 3. The electromagnetic wave absorbing sheet according to claim 1, wherein the elastic modulus is 1 / g or more.

4. The sheet-like fibrous base material has a basis weight of 30 g / m 2 4. The electromagnetic wave absorbing sheet according to claim 1, which is a nonwoven fabric as follows:

5. An electromagnetic wave absorbing sheet comprising a sheet-like fibrous substrate and a plurality of carbon nanotubes attached to the sheet-like fibrous substrate, The amount of carbon nanotubes attached is 5 mass% or more, The surface resistance is 20 Ω / sq. or more, The BET specific surface area of ​​the carbon nanotubes is 600 m 2 / g or more 2000m 2 / g or less, The basis weight of the fibrous base material is 6 g / m 2 or more and 50 g / m 2 or less, An electromagnetic wave absorbing sheet having a transmission attenuation rate of 40 dB or more in the range of 10 GHz or more and 40 GHz or less.

Citation Information

Patent Citations

  • Synthetic fiber, synthetic fiber yarn or fiber structure having carbon NANO tubes adhered thereto and method for producing these

    JP2010261108A

  • Electromagnetic wave shielding carbon nanotube coating liquid, and electromagnetic wave shielding material

    JP2018203969A

  • Electromagnetic wave-absorbing body, and method for manufacturing same

    WO2015093600A1